TINGKAT KESESUAIAN RUANG PUBLIK DENGAN KONSEP LIVABLE CITY DI KOTA SURAKARTA - Ifni Farida; Galing Yudana; Erma Fitria Rini (Universitas Sebelas Maret Surakarta, 2017)
Abstract: Development of the urban population in Indonesia that growing rapidly these days, of course will cause impacts for the city itself, including in terms of environmental degradation. Therefore, society needs of a comfortable and livable city is getting higher, which is known as the concept of livable city. One of the key principles of the concept of livable city is the availability of public space as a place to socialize and interact. Surakarta, within 5 (five) years, being actively promote provision of public green space, as one of the public space, as evidenced by the increase of public green space area 23,16% in 2016. In a study titled Indonesia Most Livable City Index, Surakarta has a livable city index reached 69,38% above the national average. The problem in this research is how the level of conformity of the public space in Surakarta with the concept of livable city? This study aims to determine the level of conformity of the public space in Surakarta with the concept of livable city, which covers several aspects, including: availability, coverage, accessibility, comfort, amenity, and supporting activity. The method in this study using deductive research approach and scoring analysis technique. Based on the analysis, it can be seen that the level of conformity of the public space in Surakarta with the concept of livable city included into the category of medium-level conformity. Nonetheless, it needs improvement in some aspects of public space in Surakarta whose value is still low, in order to realize the public space in Surakarta according to the concept of livable city. Keywords: level of conformity, public space, livable city, scoring analysis